Clinical experience with left main coronary artery stenosis. Issue 1 (January 1976) - Banim, S O; Donaldson, R M; Russell, D C; Sturridge, M F; Wright, J E; Honey, M; Balcon, R
Abstract : We report the clinical features and the results of investigation and surgery in 20 patients with significant left main coronary artery stenosis. All had moderate to severe angina; 8 had pain at rest. Three had dyspnoea as a major symptom. The electrocardiogram was abnormal in 17, with evidence of previous myocardial infarction in 10. Of the 11 patients exercised, 8 developed chest pain. Nine patients had a normal left ventriculogram. At coronary angiography all patients had major disease elsewhere in addition to the left main coronary artery stenosis. There were no deaths or major complications associated with this investigation. One patient was unsuitable for surgery because of diffuse left ventricular hypokinesia, one had a fatal myocardial infarction while awaiting operation, and there was one preoperative death. Sixteen of the 17 surgical survivors are free from angina. There has been a significant improvement in the maximum exercise capacity in the 10 patients who had pre- and postoperative exercise tests.